Techno-economic analysis of a Liquid Air Energy Storage (LAES) for cooling application in hot climates - Tafone, Alessio (2017)
This work investigates the technical and economic feasibility of a Liquid Air Energy Storage (LAES) for building demand management applications. The thermodynamics and processes of the LAES configuration, as well as the description of the daily cooling energy demand profile, are described in details and the assumptions and constrains are pointed out. The quantitative comparison has been carried out for a daily cooling energy demand of an existing office building, located in Singapore, locality characterized by a typical hot climate. A thermodynamic optimization has been carried out for LAES configuration by means of the numerical software Aspen HYSYS®. Under the technical assumptions formulated, LAES achieves a round trip efficiency of 45% with a specific consumption of 0.19 kWh/kgLA. Finally, the economic results show that under the actual condition of peak tariff and off-peak tariff in Singapore, the investment proposed is not convenient but in case of high values of LAES round trip efficiency and lower OPT the investment may be attractive. However, future works has to deal with the limitations introduced in the analysis, such as neglecting LAES operation costs, and the uncertainty related to capital costs figures.